Food, agriculture, and economic policy in the Middle East and North Africa - Lofgren, Hans (JAI Press, Inc., 2003)
The fifth volume in the series, Research in Middle East Economics focuses on crucial questions concerning the economics of food and agriculture in the Middle East and North Africa (MENA). Bringing together specialists from a number of disciplines, including agricultural economics, agronomy, economics, geography, and political science, the volume explores a range of issues of relevance to development policy makers and scholars alike. In addition to including general chapters providing discussions of the links between agriculture, food production and distribution, trade, resource use, and and government policies, the volume also contains chapters focusing on these issues for particular countries, within MENA. -- Preface, p. xii.